2012
DOI: 10.1097/spc.0b013e328352edff
|View full text |Cite
|
Sign up to set email alerts
|

Pain in neurological conditions

Abstract: Pain in neurological disease displays great diversity in putative mechanisms and clinical presentation. Rational management requires an analysis of likely mechanisms of pain generation as a guide to treatment. Some common neurological disorders are briefly discussed, primarily to provide an indication of the range of pain phenotypes observed across the spectrum of neurological disease. Treatments are reviewed with an emphasis on systemic drugs and the current best evidence for their use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Clinicians working with patients with neurological and psychiatric disorders are familiar with the fact that there are some common difficulties that their patients experience, such as sleep problems, difficulties with affect, maintaining personal relationships and holding a job. There is also research that supports this clinical experience [ 4 , 5 , 9 11 ]. Finally, it is well known that co-morbidity within brain disorders is very high, making it more intuitive to detach PSD from specific brain disorders [ 3 ].…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Clinicians working with patients with neurological and psychiatric disorders are familiar with the fact that there are some common difficulties that their patients experience, such as sleep problems, difficulties with affect, maintaining personal relationships and holding a job. There is also research that supports this clinical experience [ 4 , 5 , 9 11 ]. Finally, it is well known that co-morbidity within brain disorders is very high, making it more intuitive to detach PSD from specific brain disorders [ 3 ].…”
Section: Introductionmentioning
confidence: 77%
“…They found no study that systematically examined the difficulties associated with the full range of brain disorders. Where comparisons across brain disorders are targeted, these are usually restricted to single PSD, mostly body functions such as fatigue [ 4 ] or pain [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent review concluded that exercise with BFR may be an effective pain management strategy for people with musculoskeletal conditions 29) . Pain is also common in neurologic conditions 30) , and two feasibility trials of BFR in people with MS and SCI have both shown that resistance training with BFR at least does not increase pain or delayed onset muscle soreness compared to training without BFR 20,22) . Altogether, efficacy research is needed for exercise with BFR in people with neurologic conditions, and the results of this survey suggest that outcomes of strength, fatigue, and pain may be especially important to consider.…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms are many and vary from patient to patient. Pain phenotypes are not always specific to a neuropathy, and pain can result from neuropathy as well as from medications taken to treat the condition (Nandi, 2012). Patients may present multiple pain phenomena simultaneously, and their pain phenotypes can change over time.…”
Section: Neuropathic Painmentioning
confidence: 99%
“…Several groups of drugs have been utilized in neuropathic pain treatment; among them are analgesics like opiates, anti-inflammatory drugs including steroids, tricyclic antidepressants, anticonvulsants, antiepileptics, antihypertensives, local anesthetics, sodium channel blockers, NMDA receptor antagonists, SSRIs (selective serotonin-reuptake inhibitors), and cannabinoids (Moulin, 1998; Pöllmann and Feneberg, 2008; Park and Moon, 2010; Nandi, 2012). Side effects are common, and the use of nearly all these medications is complicated by concerns about their safety and efficacy.…”
Section: Neuropathic Painmentioning
confidence: 99%